Heart transplantation in the era of the SARS‐CoV‐2 pandemic: Is it safe and feasible?. Issue 10 (24th July 2020) - Esmailian, Gabriel; Kobashigawa, Jon A.; Nishihara, Keith; Patel, Jignesh K.; Czer, Lawrence; Megna, Dominick; Emerson, Dominic; Ramzy, Danny; Trento, Alfredo; Chikwe, Joanna; Esmailian, Fardad
Abstract: As the SARS‐CoV‐2–pandemic continues to unfold, the number of heart transplants completed in the United States has been declining steadily. The current case series examines the immediate short‐term outcomes of seven heart transplant recipients transplanted during the SARS‐CoV‐2 pandemic. We hope to illustrate that with proper preparation, planning, and testing, heart transplantation can be continued during a pandemic. We assessed 7 patients transplanted from March 4, 2020, to April 15, 2020. The following endpoints were noted: in‐hospital survival, in‐hospital freedom from rejection, in‐hospital nonfatal major cardiac adverse events (NF‐MACE), severe primary graft dysfunction, hospital length of stay, and ICU length of stay. There were no expirations throughout the hospital admission. In addition, there were no patients with NF‐MACE or treated rejection, and 1 patient developed severe primary graft dysfunction. Average length of stay was 17.2 days with a standard deviation of 5.9 days. ICU length of stay was 7.7 days with a standard deviation of 2.3 days. Despite the decreasing trend in completed heart transplants due to SARS‐CoV‐2, heart transplantation appears to be feasible in the immediate short term. Further follow‐up is needed, however, to assess the impact of SARS‐CoV‐2 on post–heart transplant outcomes months after transplantation.